Some Properties of Motion Equations Describing the Nonlinear Dynamical Response of a Multibody System with Flexible Elements - Maria Luminiţa Scutaru; Sorin Vlase (Journal of Applied Mathematics)
The industrial applications use instruments and machines operating at high speeds, developing high forces, low temperatures, corrosive environments, extreme pressures, and so forth. Under these conditions, the elasticity of elements such a machine is built of cannot be ignored anymore, and models are needed to more accurately “grasp” the mechanical phenomena accompanying the operation. The vibrations and the loss of stability are the main effects occurring under these conditions. For the study on this kind of systems with rigid motion and elastic elements, numerous models have been elaborated, the main idea being the discretization of the elements and the use of finite element method. Finally, second-order differential equations with variable coefficients are obtained; these equations are strong nonlinear ones due to the time-dependent values of angular speed and acceleration, and they can be linearized considering a very short period of time, in which the motion is considered to be “frozen.” The aim of this paper is to present some characteristic properties of these systems.